A defective release of host defense peptides is present in canine atopic skin. (August 2019) - Santoro, Domenico; Archer, Linda; Kelley, Karen
Abstract: The use of dogs as animal model for human atopic dermatitis (AD) is well known. Striking similarities in the pathogenesis of AD have been demonstrated. Similar alteration of host defense peptides (HDP) have been identified in both species. However, the ultrastructural/molecular alterations associated with HDPs secretion in AD have not been elucidated. We were able to use a multidisciplinary approach to investigate the secretion of HDP in canine skin. The contemporary use of indirect immunofluorescence, ELISA and scanning immune-electron microscopy gave fundamental insights in the pathomechanism of HDP alteration in AD. An increased intracellular expression and a reduced secretion of HDPs is present in atopic skin. An increased presence of HDPs was seen on the surface of atopic skin. These results suggested a defective secretion and an increased adhesion of HDPs to atopic corneocytes might be the reason of the reduced killing activity of HDPs in AD.